Langkah-langkah Mengembangkan Kemampuan Berpikir Kritis Pada Siswa - Ni Kadek Ayu Suatini (Kamaya: Jurnal Ilmu Agama, 2019)
Critical thinking is a demand in the implementation of the 2013 Curriculum. The importance of critical thinking skills is inseparable from constructive theory of thought, in the sense that the curriculum wants students to be able to have a power in terms of building a critical frame of mind, so that the output will be guaranteed in development soft skil. Given the importance of critical thinking in students, the teacher must develop the critical thinking skills of students. This article discusses (1) Definition of critical thinking (2) Benefits of Critical Thinking (3) Steps to develop critical thinking skills in students.